Measuring the effects of transdisciplinary research: the case of a social farming project. (January 2016) - Di Iacovo, Francesco; Moruzzo, Roberta; Rossignoli, Cristiano M.; Scarpellini, Paola
Highlights: We use a transdisciplinary approach to building an evaluation tool for social farming. We evaluate the used transdisciplinary process through the model defined by td-Net. We present the context, the background and the steps involved in the process. We analyse how the transdisciplinary process generates "new and shared" knowledge. We discuss strengths, limitations and lesson learned emerged from the process. Abstract: Social farming (SF) is an innovative concept belonging to a grey zone occupied by agriculture, social, education and health sectors. It involves various private and public actors who work together to co-create and share new collective knowledge. SF initiatives also involve many policies and tools that need to be reframed in order to facilitate the evaluation of these practices. Research in SF includes the active role of researchers in medium-term initiatives, involving a large number of stakeholders. Thus an evaluation of SF practices is crucial in developing and planning future actions. The complex nature of SF has led to the use of a transdisciplinary approach for the evaluation of its initiatives. This paper explains the transdisciplinary process used in a SF project, describes the nature of the collaborative relationships between researchers and others stakeholders, and examines the factors that inhibit and facilitate this collaboration. The paper highlights the important effects the transdisciplinary approach could have on the future of SF, in terms of network building, the co-production of knowledge, and the development of innovative practices.